Prevalência de lesões em praticantes de treinamento resistido - Indicatti, Juliano (My University, 2019)
With the search for different sports becoming increasingly precocious and sports that were previously considered recreational only becoming increasingly competitive, there has been an increasing number of injuries. Studies indicate a high number of injuries due to resistance training, suggesting the relationship of these injuries with incorrectly performed exercises, inadequate training methods, use of excessively high loads and lack of professional follow-up. Objective: To evaluate the prevalence of injuries in resistance training practitioners in a gym in Caxias do Sul-RS. Materials and Methods: Quantitative, descriptive and exploratory research with cross bias. For convenience, the sample consisted of 173 individuals, 112 males and 61 females, aged between 18 and 70 years, attending a gym in the city of Caxias do Sul, located in the state of Rio Grande do Sul. Results: Through data analysis, it was found that of 173 research participants, 33.5% have already suffered injuries due to resistance training, with a higher prevalence observed in male practitioners. The main injuries found were contracture (14%) and low back pain (14%), while the most affected body regions were shoulder (27%) and lumbar (20%). Regarding the reason why participants believe the injury occurred, the most cited option was overload (19%). Conclusion: With the data collected we can conclude that there is a considerable prevalence of injuries among practitioners of the sport, with the highest prevalence in male participants and the most affected body segment was the shoulder, and overweight reported as the main factor. of the lesions (sic).
Com a procura por diferentes modalidades esportivas se tornando cada vez mais precoce e os esportes que antes eram considerados apenas recreativos se tornando cada vez mais competitivos, tem se observado um número crescente de lesões. Estudos indicam um elevado número de lesões em decorrência do treinamento resistido, sugerindo a relação destas lesões com exercícios realizados incorretamente, métodos de treino inadequados, utilização de cargas demasiadamente elevadas e falta de acompanhamento profissional. Objetivo: Avaliar a prevalência de lesões em praticantes de treinamento resistido em uma academia de Caxias do Sul- RS. Materiais e Métodos: Pesquisa quantitativa, descritiva e exploratória com viés transversal. A amostra, por conveniência, contou com 173 indivíduos, sendo 112 do sexo masculino e 61 do sexo feminino, com idade entre 18 a 70 anos, frequentadores de uma academia da cidade de Caxias do Sul, localizada no estado do Rio Grande do Sul. Resultados: Através da análise de dados, foi constatado que dos 173 participantes da pesquisa, 33,5% já sofreram lesões devido ao treinamento resistido, sendo observada uma maior prevalência em praticantes do sexo masculino. As principais lesões constatadas foram contratura (14%) e lombalgia (14%), enquanto as regiões do corpo mais afetadas foram ombro (27%) e lombar (20%). Em relação ao motivo pelos quais os participantes acreditam ter ocorrido à lesão, a opção mais citada foi excesso de carga (19%). Conclusão: Com os dados coletados podemos concluir que existe uma considerável prevalência de lesões entre os praticantes da modalidade, sendo a maior prevalência nos participantes do sexo masculino e o segmento corporal mais afetado foi o ombro, sendo o excesso de carga relatado como o principal fator das lesões (sic).
Keywords: Exercícios físicos; Ferimentos e lesões